Controlled release of anti-diabetic drug metformin hydrochloride from cellulose/PEG/poly (SA) ter-polymeric hydrogels. Issue 3 (4th March 2017) - Bajpai, S. K.; Swarnkar, M. P.
ABSTRACT: In the present work, cellulose pulp, obtained from a paper industry, has been dissolved in PEG/NaOH system and the resulting solution has been polymerized in the presence of monomer sodium acrylate (SA) and crosslinker N, N' methylene bisacrylamide (MB) via free radical polymerization. These gels have been loaded with anti-diabetic drug Metformin Hydrochloride (Met) and a detailed investigation of release of drug has been studied. Various kinetic models have been applied on the release data. Finally, the in-vivo study has been carried out on albino Wistar rats to see the efficacy of these hydrogel systems in lowering the glucose level.